(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Sediment contamination is one of the major challenges the Euphrates River environment faces. The Euphrates River is regarded as the main supply of water for industrial and agricultural purposes for Samawa City in Al Muthanna Province, the southwestern part of Iraq. The sewage pipeline is dumped into the river, which directly affects the water quality and subsequently the vegetation. A magnetic mineralogy study is carried out on sediments to specify the contamination by heavy metals. Magnetic properties are measured in 250 sediment samples; magnetic susceptibility, anhysteretic remanent magnetization, isothermal remanent magnetization, and thermomagnetic analyses are measured. Heavy metal analyses are performed using SEM together with energy-dispersive X-ray and X-ray fluorescence analyses to connect the results with magnetic enhancements. Statistical analyses show that the mean value of magnetic susceptibility is 3361.2 × 10-8 m3kg-1, of anhysteretic remanent magnetization is 628.9 × 10-8 m3kg-1, and thermomagnetic analyses (high and low) clearly show the typical curves of magnetite. The magnetic properties results indicate that the main magnetic phases are single-domain (SD) to multi-domain (MD) state magnetite caused by the surrounding catchment and anthropogenic activities. Results of heavy metal (HM) analysis performed on ten selected samples and then compared with the magnetic results. A correlation between HM and χ shows a positive correlation between magnetic susceptibility and Ca, Cr, Mg, Fe, Pb, and Na concentrations. The results of magnetic mineralogy indicate that the magnetic susceptibility parameter can be used as an indicator for heavy metals.